Maxing out: the puzzling influence of past maximum returns on future asset prices in a cross-country analysis - Yuan, Shuonan (Springer Nature, 2020)
We examine the role of extreme positive returns in the cross-section of stock returns in seven countries. While Bali et al. (J Financ Econ 99:427–446, 2011) ﬁnd a signiﬁcantly negative relation between the maximum daily returns over the past month (MAX) and the expected returns in the following month, we ﬁnd that this relation disappears and even often reverses. The positive relation is found in Canada, the UK and the US, while the pattern in China is more in line with the previous ﬁndings, and for Germany, France and Japan the effect is not statistically signiﬁcant. Further evidence using the US data suggests that the positive effect of MAXis largely a proxy for the idiosyncratic volatility. Moreover, we ﬁnd that the MAX effect is mainly concentrated on periods before 1990’s given the same dataset as Bali et al. (2011). Collectively, our results indicate that the MAX effect is not stable over time. We conjecture the changing proportion of MAX-seeking investors is a crucial determinant of the MAX-return relation.